2015
DOI: 10.1183/16000617.00002515
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal immunity and novel tuberculosis vaccine strategies: route of immunisation-determined T-cell homing to restricted lung mucosal compartments

Abstract: Despite the use of bacille Calmette-Guérin (BCG) for almost a century, pulmonary tuberculosis (TB) continues to be a serious global health concern. Therefore, there has been a pressing need for the development of new booster vaccines to enhance existing BCG-induced immunity. Protection following mucosal intranasal immunisation with AdHu5Ag85A is associated with the localisation of antigen-specific T-cells to the lung airway. However, parenteral intramuscular immunisation is unable to provide protection despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Further experiments, will address the ability of B–C–M to induce antigen specific memory responses and to provide durable protection when mice are challenged much later after vaccination. In addition, the distribution of antigen-specific T cells in different lung compartments will be further explored [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Further experiments, will address the ability of B–C–M to induce antigen specific memory responses and to provide durable protection when mice are challenged much later after vaccination. In addition, the distribution of antigen-specific T cells in different lung compartments will be further explored [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of immunity, especially manipulating antigens to be more efficiently presented by antigen-presenting cells (APCs) that can activate the effector T and B cells of the immune defense is a major goal in treatment and prevention of bacterial or viral infections (Lai et al, 2015 ). The respiratory tract is the portal of entry for M.tb (Rodriguez et al).…”
Section: Discussionmentioning
confidence: 99%
“…Although human BCG today is primarily administered through the intradermal route, oral BCG administration has a long history and was used in multiple controlled studies performed in the 1920s and 1930s; demonstrating significant protection against TB (Aronson & Dannenberg, ; Kerszturi, ). More recent studies showed that oral BCG administration induces mucosal immunity, with enhanced TB‐specific secretory IgA, T‐cell homing to restricted lung mucosal compartments and bronchoalveolar lavage recovery of these T‐cells, compared to intradermal vaccination (Hoft et al., ; Lai, Afkhami, Haddadi, Jeyanathan, & Xing, ). In studies using rhesus macaques, pulmonary mucosal BCG vaccination conferred enhanced protection compared to standard intradermal BCG (Verreck et al., ), and it seems preferable to match the route of vaccination and natural infection (Manjaly & McShane, ).…”
Section: Efficacy Of Oral Bcgmentioning
confidence: 99%